Implementation of a structured patient handoff between health care providers at a private facility in the Autonomous City of Buenos Aires - García Roig, Cristian (2020)
Introduction. Failures in communication are common during patient handoffs between physicians, which predisposes to errors. Few articles have been published on this topic in Argentina. For this reason, our objective was to confirm whether using a structured handoff (I-PASS), which has been successfully used in the USA by Doctor Starmer, may reduce the omission of key data without prolonging its duration at our department. Population and methods. The study was conducted at a private facility in the Autonomous City of Buenos Aires between June 15th, 2017 and March 31st, 2018. It had a quasi-experimental, uncontrolled, before-and-after design. Pre- A nd post-intervention handoffs were assessed. The intervention included training physicians on how to use a structured handoff mnemonic (I-PASS: Illness severity, patient summary, action list, situation awareness and contingency planning, synthesis by receiver), training on team work, written computerized handoff document, feedback observations, and simulation. Results. A total of 158 and 124 pre- A nd post-intervention assessments were done respectively. The pre- A nd post-intervention comparison showed a significant improvement in most of the handoff key points. The time used for the handoff was 199 seconds (174-225) before the intervention and 210 seconds (190-230) after the intervention, p = 0.523; interruptions also decreased significantly. Conclusion. Introducing the I-PASS program reduced key data omission without prolonging handoffs. Interruptions were also reduced.